2016
DOI: 10.1002/smi.2711
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the work–family conflict and health link: Repetitive thought as a mechanism

Abstract: Research is needed to investigate mechanisms linking work-family conflict to poor health in working adults. We took a novel approach to build on extant studies by testing a potential mechanism in these associations - repetitive thought. Data came from a sample of 203 partnered working adults. There were significant direct effects of work-family conflict with lower life satisfaction, positive affect, and perceived health as well as greater fatigue. As for total effects, work-family conflict was significantly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 55 publications
6
44
0
4
Order By: Relevance
“…Previous research has also investigated some of the cognitive mechanisms underlying the relationship between WLC and positive/negative affect. For example, repetitive thinking about the conflict (i.e., repetitive thought) mediates the relationship between WFC and positive/negative affect (Davis, Gere, & Sliwinski, ). Furthermore, in the mediation models, Davis et al () found a significant direct effect between WFC and positive affect, but no direct effect for WFC and negative affect, suggesting that for WFC, repetitive thought may be a primary mechanism.…”
Section: Psychological Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also investigated some of the cognitive mechanisms underlying the relationship between WLC and positive/negative affect. For example, repetitive thinking about the conflict (i.e., repetitive thought) mediates the relationship between WFC and positive/negative affect (Davis, Gere, & Sliwinski, ). Furthermore, in the mediation models, Davis et al () found a significant direct effect between WFC and positive affect, but no direct effect for WFC and negative affect, suggesting that for WFC, repetitive thought may be a primary mechanism.…”
Section: Psychological Health Outcomesmentioning
confidence: 99%
“…Generally, higher WLC has been linked to increased physical and physiological symptoms. Some studies have found support for a direct relationship between WLC and physical health (e.g., Lee et al, ), while others found support for an indirect relationship (e.g., Davis et al, ). As discussed earlier, distress can mediate the relationship between WFC and physical health (Grandey & Cropanzano, ).…”
Section: Physical and Physiological Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies indicated that nurses’ exposure to high‐stress environments can lead to physical and psychological problems, such as work–family conflicts (WFCs) (Chu, ; Ghislieri, Gatti, Molino, & Cortese, ), impaired sleep (Hasson & Gustavsson, ; Lin et al, ; Lin, Liao, Chen, & Fan, ) and poor health (Jordan et al, ). WFCs and poor sleep were reported to impair the health of working women (Buxton et al, ; Davis, Gere, & Sliwinski, ). WFCs are also known to affect sleep quality (Aazami, Mozafari, Shamsuddin, & Akmal, ).…”
Section: Introductionmentioning
confidence: 99%
“…We assessed physical health with self-reports of health conditions, self-rated general health, and severity of physical health symptoms. Participants first reported whether they had 25 different health conditions (e.g., diabetes, high blood pressure; adapted from Davis, Gere, & Sliwinski, 2017), which were summed to create a score for a number of health conditions (M = 2.18, SD = 2.49, range: 0-22). 1 Next, participants rated their general health using one item ('For your age, would you rate your physical health as excellent, good, fair, or poor'; 1 = poor; 4 = excellent), a robust predictor of actual physical health (DeSalvo, Bloser, Reynolds, He, & Muntner, 2006; M = 2.63, SD = 0.73, range: 1-4).…”
Section: Physical Healthmentioning
confidence: 99%